2020
DOI: 10.1111/jfs.12866
|View full text |Cite
|
Sign up to set email alerts
|

Detection for lead pollution level of lettuce leaves based on deep belief network combined with hyperspectral image technology

Abstract: Fast detection for heavy metal in vegetables is one of the most important steps to ensure the food safety. A novel method to identify lead pollution levels of lettuce based on hyperspectral image technology was proposed in this study. Firstly, hyperspectral images of lettuce samples cultivated under four lead stress levels (0 mg/L, 50 mg/L, 100 mg/L and 200 mg/L) were collected using hyperspectral image system. Then, a total of 240 spectra were calculated from region of interest (ROI) in the range of 478–978 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…It can be seen that when the the concentration of Pb stress in rape leaves was 100 mg/L, the SPAD value was higher than that of the ck group without Pb stress, indicating that the low concentration of Pb can increase the SPAD value and promote the production of chlorophyll. When the concentration of Pb stress was more than 100 mg/L, SPAD value decreased with the increase of Pb content, indicating that excessive Pb concentration in leaves can inhibit the production of chlorophyll (Sun et al, 2021). With the increase of chlorophyll content in rape leaves, photosynthesis was enhanced, and the absorption of red and blue light was increased, leading to the gradual decrease of its reflectivity (Fang, Song, Cao, He, & Qiu, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that when the the concentration of Pb stress in rape leaves was 100 mg/L, the SPAD value was higher than that of the ck group without Pb stress, indicating that the low concentration of Pb can increase the SPAD value and promote the production of chlorophyll. When the concentration of Pb stress was more than 100 mg/L, SPAD value decreased with the increase of Pb content, indicating that excessive Pb concentration in leaves can inhibit the production of chlorophyll (Sun et al, 2021). With the increase of chlorophyll content in rape leaves, photosynthesis was enhanced, and the absorption of red and blue light was increased, leading to the gradual decrease of its reflectivity (Fang, Song, Cao, He, & Qiu, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The absorption of Pb by plants can cause changes in chlorophyll content of leaves, affecting the spectral reflectance of visible light band. In addition, the structure of leaf membrane system can be destroyed by Pb stress, and the reflectance of near‐infrared band can be changed (Liang, Shi, Ma, Xing, & Yu, 2010; Sun et al, 2021). Therefore, the Pb content of rape leaves can be reflected by analyzing the spectral data of hyperspectral.…”
Section: Introductionmentioning
confidence: 99%
“…We selected 10 symmetrically distributed ROIs for each hyperspectral image. The average of the spectra in each ROI were used as sample spectra for that moment, and each moment contained 30 spectra, for a total of 180 spectra [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent advances in machine learning have shown that deep learning algorithms can automatically learn to extract features from raw data and significantly improve modeling performance for many spectral analysis tasks ( Singh et al, 2018 ; Kanjo et al, 2019 ; Rehman et al, 2020 ). Sun et al (2019 , 2021) employed a deep brief network to estimate cadmium and lead contents of lettuces with high accuracy. Rehman et al (2020) also developed a modified Inception module to predict the relative water content (RWC) of maize leaves and achieved a determination coefficient ( R 2 ) of 0.872 for RWC.…”
Section: Introductionmentioning
confidence: 99%